A Wizard for Composing SPARQL Queries in the GF Framework for Ontology-Based Data Access - Gómez, Sergio Alejandro (2022)
Ontology-Based Data Access is a methodology concerned with bridging the gap between legacy data sources and semantic web technologies by providing protocols and tools for translating old data into ontologies. Querying modern ontologies represented as networks of objects interlinked by relations and properties and stored in OWL/RDF text files requires writing SPARQL queries, an activity requiring technical proficiency that is not usually in the hands of lay users. We extend our prototype of OBDA called GF to include the functionality of executing arbitrary SPARQL queries posed against OWL/RDF ontologies obtained by OBDA from H2 relational databases as well as Excel and CSV spreadsheets. To help naive users with less technical programming skills perform queries on such ontologies, we introduce a wizard for visually expressing a subset of SPARQL queries in a Query-By-Example approach.